Markov evolutions and hierarchical equations in the continuum. II: multicomponent systems - Finkelshtein, Dmitri L. (2015)
General birth-and-death as well as hopping stochastic dynamics of infinite multicomponent particle systems in the continuum are considered. We derive the corresponding evolution equations for quasi-observables and correlation functions. We also present sufficient conditions that allow us to consider these equations on suitable Banach spaces.